Modified Iterative Method for Solving Sine - Gordon Equations - Yassein, Samaher M. (Iraqi Journal of Science, 2023)
The basic goal of this research is to utilize an analytical method which is called the Modified Iterative Method in order to gain an approximate analytic solution to the Sine-Gordon equation. The suggested method is the amalgamation of the iterative method and a well-known technique, namely the Adomian decomposition method. A method minimizes the computational size, averts round-off errors, transformation and linearization, or takes some restrictive assumptions. Several examples are chosen to show the importance and effectiveness of the proposed method. In addition, a modified iterative method gives faster and easier solutions than other methods. These solutions are accurate and in agreement with the series of solutions that are provided by analytical results. To evaluate the outcomes in the modified iterative process, we have used the Matlab symbolic manipulator.